Protein Arginine Methyltransferase 5 Promotes Esophageal Squamous Cell Carcinoma Proliferation and Metastasis via LKB1/AMPK/mTOR Signaling Pathway - Yu-ru Chen; Hua-ni Li; Lian-jun Zhang; Chong Zhang; Jin-guang He (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) is the eighth most common cancer in the world. Protein arginine methyltransferase 5 (PRMT5), an enzyme that catalyzes symmetric and asymmetric methylation on arginine residues of histone and non-histone proteins, is overexpressed in many cancers. However, whether or not PRMT5 participates in the regulation of ESCC remains largely unclear.Methods: PRMT5 mRNA and protein expression in ESCC tissues and cell lines were examined by RT-PCR, western blotting, and immunohistochemistry assays. Cell proliferation was examined by RT-PCR, western blotting, immunohistochemistry assays, MTT, and EdU assays. Cell apoptosis and cell cycle were examined by RT-PCR, western blotting, immunohistochemistry assays, and flow cytometry. Cell migration and invasion were examined by RT-PCR, western blotting, immunohistochemistry assays, and wound-healing and transwell assays. Tumor volume, tumors, and mouse weight were measured in different groups. Lung tissues with metastatic foci, the number of nodules, and lung/total weight were measured in different groups.Results: In the present study, the PRMT5 expression level was dramatically upregulated in ESCC clinical tissues as well as ESCC cell lines (ECA109 and KYSE150). Furthermore, knocking down PRMT5 obviously suppressed cell migration, invasion, proliferation, and cell arrest in G1 phase and promoted cell apoptosis in ESCC cells. Meanwhile, downregulating PRMT5 also increased the expression levels of Bax, caspase-3, and caspase-9, while expression levels of Bax-2, MMP-2, MMP-9, and p21 were decreased, which are members of the cyclin-dependent kinase family. Furthermore, knocking down PRMT5 could increase the expression of LKB1 and the phosphorylation (p)-AMPK expression and decrease the p-mTOR level. Additionally, overexpression of LKB1 could reveal anti-tumor effects in ESCC cell lines by inhibiting ESCC cell, migration, invasion, and proliferation and accelerating cell apoptosis. Besides, upregulating LKB1 expression could increase the levels of Bax, caspase-3, and caspase-9 and weaken the levels of Bax-2, MMP-2, and MMP-9. Moreover, knocking down PRMT5 could weaken the tumor growth and lung metastasis in vivo with upregulating the LKB1 expression and the p-AMPK level and downregulating the p-mTOR expression.Conclusion: PRMT5 may act as a tumor-inducing agent in ESCC by modulating LKB1/AMPK/mTOR pathway signaling.